Composite action of octagonal concrete-filled steel tubular stub columns under axial loading. (October 2016) - Ding, Fa-xing; Li, Zhe; Cheng, Shanshan; Yu, Zhi-wu
Abstract: This paper presents a combined experimental, numerical and theoretical study on the mechanical performances of octagonal CFT stub columns subjected to axial compressive loading. Eight specimens of axial compression tests have been carried out aiming at investigating the effects of the concrete strength and steel ratio on the mechanical and deformed behavior of octagonal CFT stub columns. 3D finite element modelling was established for parametric studies to probe into the composite action between the steel tube and the core concrete of the octagonal CFT stub column. In addition, a practical formula has been proposed to predict the ultimate bearing capacity of the octagonal CFT stub column with the confinement coefficient of 1.5, which is an amplification coefficient of the vertical bearing capacity of steel tube considering the composite action between the core concrete and the steel tube. Highlights: The shape of steel tube is octagon. A 3D FE model is developed to analyze the mechanical properties of the CFT columns. There exists a significant composite action between the steel tube and the core concrete. A practical formula for the octagonal CFT stub columns is proposed.